Short- to Intermediate-Range Structure, Transport, and Thermophysical Properties of LiF–NaF–ZrF4 Molten Salts - Chahal, Rajni; Banerjee, Shubhojit; Lam, Stephen T. (Frontiers in Physics, 2022)
LiF – NaF – ZrF4 multicomponent molten salts are identified as promising candidates for coolant salts in molten salt reactors and advanced high-temperature reactors. This study focused on low-melting point salt compositions of interest: 38LiF – 51NaF – 11ZrF4, 42LiF – 29NaF – 29ZrF4, and 26LiF – 37NaF – 37ZrF4. Ab-initio molecular dynamics (AIMD) calculations were performed and compared with available experimental data to assess the ability of polarizable ion models (PIM) to reproduce short to intermediate-range structure, transport and thermophysical properties of the LiF – NaF – ZrF4 salt mixtures. It is found that as ZrF4 mol% increases, the average cation-anion coordination number (CN) of monovalent cations (Li+, Na+) obtained from PIM calculations decreases, while multivalent Zr4+ CN varied from 15-19% in comparison to corresponding AIMD values. In addition, PIM is found to predict the existence of 7, 8, and 9-coordinated fluorozirconate complexes, while AIMD and the available experimental data showed occurrence of 6, 7, and 8 coordinated complexes in the melt. The intermediate-range structure analysis revealed that while the PIM parameters are able to reproduce local structure for lower ZrF4 mol%-salts such as in 38LiF – 51NaF – 11ZrF4, an extensive fluorozirconate network formation is observed in PIM simulations for higher ZrF4 mol% compositions. The network generated by PIM parameters is found to be mainly connected by “corner-sharing” fluorozirconate complexes as opposed to both “edge-sharing” and “corner-sharing” connectively portrayed by AIMD. It is found that close agreement between AIMD and PIM salt structure for the 11 mol% ZrF4 salt resulted in good agreement in the calculated Zr diffusivities and the viscosity values. However, due to the inaccurate short to intermediate-range structure prediction by PIM for higher ZrF4 mol% compositions, thermophysical properties such as densities and heat capacity differ by up to 26% and 27%, respectively upon comparison with AIMD and experimental values. Also, the network dominated properties such as diffusion coefficients and viscosities are overpredicted by up to two and three orders of magnitude, respectively. This study signifies the importance of accurate salt structure generation for accurate prediction of transport and thermophysical properties of multicomponent molten salts.